Locusts: protecting thornbushes or feeding people - a choice - Skaf, Rafik (Technical Centre for Agricultural and Rural Cooperation, 1988)
Rafik Skaf Dr Rafik Skaf, who retired in January 1988, worked for 23 years at FAO where since 1980, he was Director of the 'Locusts, Migrating Pests and Emergency Operations Group'. He was previously Director of Plant Protection for 16 years in...